THE EFFECT OF PLANT AVAILABILITY ON LIFE CYCLE PERFORMANCE OF COAL FIRED POWER STATIONS (International Journal of Engineering and Computer Science, 2013)
This paper seeks to identify production and maintenance problems that are related to key availability factors such as times to failure (reliability), repair times (maintainability) and waiting times (maintenance support) and use them as a yardstick for adjudging the efficacy of Availability Centred Maintenance, (ACM) using the Pareto analysis for the significant failures. It also explores the possibility of import substitution, and spare part interchangeability and the implementation of internationally recognised standards such as, ISO 9000, ISO 14 000, use of Pareto analysis to establish the unavailability and downtime cost significance regime. The research then recommends the possible use of FMECA to those statistically or maintenance significant (ABC) items. The paper further recommends the implementation of softer aspects of maintenance management such as performance based contracts, benchmarking and identification of training needs. Keywords:Availability Cenred Maintanance, Availability, Pareto Analysis, ISO